Structure with copper plating layer or copper alloy plating layer, and method for manufacturing same
By forming a copper plating layer or copper alloy plating layer with a controlled change in cathode current density, the formation of Kirkendall voids is suppressed, addressing the reliability issues at the interfaces between copper and tin or tin alloys.
Patent Information
- Application Number
- JP2021518375
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-05-08
- Filing Date
- 2020-04-30
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2040-04-30
AI Technical Summary
Existing technologies face challenges in suppressing the formation of Kirkendall voids at the interfaces between copper and tin or tin alloys, which reduces the reliability of the resulting structure. Current methods, such as adding silver to tin or forming a nickel-based diffusion barrier layer, are either difficult to control or overly complex and costly.
A copper plating layer or copper alloy plating layer is formed using electroplating with a predetermined first cathode current density, followed by a change to a second cathode current density that is lower than the first, to create a surface layer with a thickness of 0.05 μm to 15 μm, thereby suppressing the formation of Kirkendall voids.
This method allows for the manufacture of copper plating structures without complex steps, effectively suppressing the formation of Kirkendall voids and enhancing the reliability of the structure.
Smart Images

Figure 0007659899000001 
Figure 0007659899000002 
Figure 0007659899000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a structure having a copper plating layer or a copper alloy plating layer. More specifically, the present invention relates to a structure having a copper plating layer or a copper alloy plating layer that can be manufactured without complicated processes and in which the generation of Kirkendall voids (voids) is suppressed. [Background technology]
[0002] Generally, solder plating, solder balls, solder paste, etc. are used to join electrodes of electronic components to other components. For example, in semiconductor chips, when protruding electrodes (copper pillars) are used to improve electrical characteristics and accommodate fine pitches, Cu / Ni / Sn-Ag or Cu / Ni / Sn structures are formed by a plating process. Furthermore, in recent years, in order to prevent the manufacturing process from becoming complicated and costs from rising, many Cu / Sn-Ag structures are being used without a Ni layer.
[0003] However, at the bonding interface between Cu and Sn or Sn alloy, Kirkendall voids are generated due to the difference in diffusion rate of each metal, and there is a concern that the reliability of the resulting structure may be reduced.
[0004] Therefore, in order to suppress the generation of Kirkendall voids at the joint interface between metals, techniques disclosed in, for example, Patent Documents 1 and 2 have been proposed.
[0005] Patent Document 1 discloses a technology in which tin is used as the main component and silver, copper, phosphorus, antimony, bismuth, etc. are added to it to suppress the formation of intermetallic compounds at the interface between the copper pillar and the tin alloy, thereby suppressing the generation of Kirkendall voids.
[0006] Patent Document 2 discloses a technique for suppressing the generation of Kirkendall voids by forming a diffusion barrier layer containing nickel, nickel-phosphorus, nickel-vanadium, or the like on a copper-containing column layer.
[0007] However, it is virtually impossible with the plating methods currently used to control the complex metal composition as in the technique disclosed in Patent Document 1. On the other hand, if the technique disclosed in Patent Document 2 is adopted, there is a problem that the process becomes too complicated, and in addition, when cost is taken into consideration, it is often impossible to adopt such a technique. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2004-154845 A [Patent Document 2] Patent No. 5756140 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a structure having a copper-containing plating layer that can be manufactured without complicated processes and in which the generation of Kirkendall voids is suppressed. [Means for solving the problem]
[0010] The present invention (I) is The plated layer is a copper or copper alloy plated layer. The copper plating layer or copper alloy plating layer is formed by performing an electroplating process on an electric copper plating or copper alloy plating bath at a predetermined first cathode current density, and then changing the current density to a second cathode current density lower than the first cathode current density to terminate the electroplating process; the first predetermined cathode current density being a cathode current density in an electroplating process performed at a single cathode current density until a change to the second cathode current density is made; The predetermined first cathode current density is 5 A / dm 2 That's all. the layer formed by changing to the second cathode current density is a surface layer portion of the copper plating layer or copper alloy plating layer, The thickness of the surface layer is 0.05 μm to 15 μm. Regarding.
[0011] The present invention (II) is The plated layer is a copper or copper alloy plated layer. The copper plating layer or copper alloy plating layer is formed by performing an electroplating process on an electric copper plating or copper alloy plating bath at a predetermined first cathode current density, and then changing the current density to a second cathode current density lower than the first cathode current density to terminate the electroplating process; The predetermined first cathode current density is an average cathode current density calculated by the following formula (1) in an electroplating process performed by combining a plurality of cathode current densities until the predetermined first cathode current density is changed to the second cathode current density, Average cathode current density = cathode current density n1 × (Plating time n1 / total plating time) +Cathode current density n2 × (Plating time n2 / total plating time)... +Cathode current density n-1 × (Plating time n-1 / total plating time) +Cathode current density n × (Plating time n / total plating time) (1) (wherein the plurality of cathode current densities is n cathode current densities, Cathode current density n1 is the first cathode current density, Cathode current density n2 is the second cathode current density, Cathode current density n-1 is the n-1th cathode current density, Cathode current density n is the nth cathode current density, Plating Time n1 is the cathode current density n1 The plating time was Plating Time n2 is the cathode current density n2 The plating time was... Plating Timen-1 is the cathode current density n-1 The plating time was Plating Time n is the cathode current density n (The plating time was The predetermined first cathode current density is 5 A / dm 2 That's all. the layer formed by changing to the second cathode current density is a surface layer portion of the copper plating layer or copper alloy plating layer, The thickness of the surface layer is 0.05 μm to 15 μm. Regarding.
[0012] In the present invention (II), The electroplating process performed by combining a plurality of cathode current densities is an electroplating process in which the cathode current densities are sequentially increased from the start of the electroplating process to the final stage of forming the copper plating layer or copper alloy plating layer, or an electroplating process in which the cathode current density is increased and then decreased. It is preferable that: Effect of the Invention
[0013] The structure having a copper plating layer or a copper alloy plating layer of the present invention can be manufactured without complicated processes, and the formation of Kirkendall voids is sufficiently suppressed, so that the structure has high reliability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The structure of the present invention (I) and the structure of the present invention (II) have a copper plating layer or a copper alloy plating layer, and the copper plating layer or the copper alloy plating layer is formed by performing an electroplating process at a predetermined first cathode current density in an electric copper plating or copper alloy plating bath, and then changing to a second cathode current density lower than the first cathode current density and terminating the electroplating process. Note that in this specification, the present invention (I) and the present invention (II) are collectively referred to as "the present invention", and the structure of the present invention (I) and the structure of the present invention (II) are collectively referred to as "the structure of the present invention".
[0015] The electrolytic copper plating or copper alloy plating bath preferably contains, for example, one or more copper ion supplying compounds.
[0016] The copper ion supplying compound is essentially Cu in an aqueous solution. 2+ There are no particular limitations on the copper ion supplying compound, so long as it is a soluble copper salt that generates the above. Examples of the copper ion supplying compound include copper sulfate, copper oxide, copper nitrate, copper chloride, copper pyrophosphate, copper carbonate, as well as copper carboxylates such as copper acetate, copper oxalate, and copper citrate; and copper alkylsulfonates such as copper methanesulfonate and copper hydroxyethanesulfonate. One or more of these can be used.
[0017] The content of the copper ion supplying compound in the copper electroplating bath is not particularly limited, but is preferably about 1 g / L to 300 g / L, and more preferably about 30 g / L to 250 g / L.
[0018] When the plating bath used in the electroplating process is an electric copper plating bath, the copper ion supply compound may be added, whereas when the plating bath is an electric copper alloy plating bath, one or more soluble salts of a metal that forms an alloy with copper may be added.
[0019] There is no particular limitation on the metal that forms an alloy with copper, and examples thereof include nickel, silver, zinc, bismuth, cobalt, indium, antimony, tin, gold, lead, etc. As described below, when the structure of the present invention has a plating layer of a metal or metal alloy other than copper adjacent to the copper alloy plating layer, the metal that forms an alloy with copper may be selected from metals that do not constitute a plating layer of a metal or metal alloy other than copper.
[0020] Examples of soluble salts of nickel include nickel sulfate, nickel formate, nickel chloride, nickel sulfamate, nickel fluoroborate, nickel acetate, nickel methanesulfonate, and nickel 2-hydroxypropanesulfonate.
[0021] Examples of soluble silver salts include silver carbonate, silver nitrate, silver acetate, silver chloride, silver oxide, silver cyanide, silver potassium cyanide, silver methanesulfonate, silver 2-hydroxyethanesulfonate, and silver 2-hydroxypropanesulfonate.
[0022] Examples of soluble zinc salts include zinc oxide, zinc sulfate, zinc nitrate, zinc chloride, zinc pyrophosphate, zinc cyanide, zinc methanesulfonate, zinc 2-hydroxyethanesulfonate, and zinc 2-hydroxypropanesulfonate.
[0023] Examples of soluble salts of bismuth include bismuth sulfate, bismuth gluconate, bismuth nitrate, bismuth oxide, bismuth carbonate, bismuth chloride, bismuth methanesulfonate, and bismuth 2-hydroxypropanesulfonate.
[0024] Examples of soluble salts of cobalt include cobalt sulfate, cobalt chloride, cobalt acetate, cobalt fluoroborate, cobalt methanesulfonate, and cobalt 2-hydroxypropanesulfonate.
[0025] Examples of soluble salts of indium include indium sulfamate, indium sulfate, indium borofluoride, indium oxide, indium methanesulfonate, and indium 2-hydroxypropanesulfonate.
[0026] Examples of soluble salts of antimony include antimony fluoroborate, antimony chloride, potassium antimonyl tartrate, potassium pyroantimonate, antimony tartrate, antimony methanesulfonate, and antimony 2-hydroxypropanesulfonate.
[0027] Examples of soluble salts of tin include stannous sulfate, stannous acetate, stannous borofluoride, stannous sulfamate, stannous pyrophosphate, stannous chloride, stannous gluconate, stannous tartrate, stannous oxide, sodium stannate, potassium stannate, stannous methanesulfonate, stannous ethanesulfonate, stannous 2-hydroxyethanesulfonate, stannous 2-hydroxypropanesulfonate, and stannous sulfosuccinate.
[0028] Examples of soluble gold salts include potassium chloroaurate, sodium chloroaurate, ammonium chloroaurate, potassium gold sulfite, sodium gold sulfite, ammonium gold sulfite, potassium gold thiosulfate, sodium gold thiosulfate, and ammonium gold thiosulfate.
[0029] Examples of soluble salts of lead include lead acetate, lead nitrate, lead carbonate, lead fluoroborate, lead sulfamate, lead methanesulfonate, lead ethanesulfonate, lead 2-hydroxyethanesulfonate, and lead 2-hydroxypropanesulfonate.
[0030] The total content of the copper ion supply compound and the soluble salt of the metal that forms an alloy with copper in the electric copper alloy plating bath is not particularly limited, but is preferably about 1 g / L to 200 g / L, more preferably about 10 g / L to 150 g / L.
[0031] There are no particular limitations on the combination and ratio of the copper ion supply compound and the soluble salt of a metal that forms an alloy with copper, and the combination and ratio of both compounds may be appropriately adjusted so that the structure of the present invention formed from the electric copper alloy plating bath has the desired composition.
[0032] In addition to the one or more copper ion supply compounds and the one or more soluble salts of metals that form alloys with copper, various additives such as electrolytes, accelerators, polymeric surfactants, levelers, pH buffers, and chelating agents may be blended into the copper electroplating or copper alloy plating bath.
[0033] Examples of the electrolyte include acids, chlorides, nitrates, sulfates, carbonates, phosphates, acetates, and perchlorates.
[0034] Examples of the acid include nitric acid, hydrochloric acid, sulfuric acid, methanesulfonic acid, acetic acid, carbonic acid, phosphoric acid, boric acid, oxalic acid, lactic acid, hydrogen sulfide, hydrofluoric acid, formic acid, perchloric acid, chloric acid, chlorous acid, hypochlorous acid, hydrobromic acid, hydroiodic acid, nitrous acid, sulfurous acid, etc. Hydrochloric acid also acts as a chloride ion source.
[0035] The chloride acts as a chloride ion source similarly to the hydrochloric acid, and examples of the chloride include lithium chloride, sodium chloride, potassium chloride, magnesium chloride, calcium chloride, barium chloride, zinc chloride, copper(II) chloride, aluminum chloride, iron(III) chloride, and ammonium chloride.
[0036] Examples of the nitrates include sodium nitrate, potassium nitrate, magnesium nitrate, calcium nitrate, barium nitrate, zinc nitrate, silver nitrate, copper(II) nitrate, aluminum nitrate, iron(III) nitrate, ammonium nitrate, etc. Among these nitrates, copper(II) nitrate also acts as the copper ion supply compound, and zinc nitrate and silver nitrate also act as soluble salts of metals that form alloys together with copper.
[0037] Examples of the carbonate include sodium carbonate, sodium hydrogen carbonate, potassium carbonate, potassium hydrogen carbonate, and ammonium carbonate.
[0038] Examples of the phosphate include sodium phosphate, disodium hydrogen phosphate, sodium hydrogen phosphate, potassium phosphate, dipotassium hydrogen phosphate, and potassium hydrogen phosphate.
[0039] Examples of the acetate salt include sodium acetate, potassium acetate, calcium acetate, copper (II) acetate, aluminum acetate, and ammonium acetate.
[0040] Examples of the perchlorate include sodium perchlorate and potassium perchlorate.
[0041] The accelerator is a component that accelerates the formation of growth nuclei during plating deposition. Examples of the accelerator include bis(3-sulfopropyl) disulfide (also known as 3,3'-dithiobis(1-propanesulfonic acid)), bis(2-sulfopropyl) disulfide, bis(3-sulfopropyl) disulfide, H -2-hydroxypropyl) disulfide, bis(4-sulfopropyl) disulfide, bis(p-sulfophenyl) disulfide, 3-benzothiazolyl-2-thio) propanesulfonic acid, N,N-dimethyl-dithiocarbamylpropanesulfonic acid, N,N-dimethyl-dithiocarbamylpropanesulfonic acid, N,N-dimethyl-dithiocarbamic acid-(3-sulfopropyl)-ester, 3-[(aminoiminomethyl)thio]-1-propanesulfonic acid, o-ethyl-diethylcarbonic acid-S-(3-sulfopropyl) ester, mercaptomethanesulfonic acid, mercaptoethanesulfonic acid, mercaptopropanesulfonic acid, and salts thereof.
[0042] As the polymer surfactant, nonionic surfactants are particularly preferred, and examples thereof include nonionic polyether polymer surfactants such as polyethylene glycol, polypropylene glycol, Pluronic (registered trademark) type surfactants, Tetronic type surfactants, polyethylene glycol glyceryl ether, sulfonic acid group-containing polyalkylene oxide adduct amines, polyoxyethylene alkyl ether, bisphenol A polyethoxylate, and sodium alkylnaphthalene sulfonate.
[0043] The leveler (smoothing agent) has a function of suppressing electrodeposition and acts to smooth the electrodeposition film. The leveler is preferably selected from, for example, amines, dyes, imidazolines, imidazoles, benzimidazoles, indoles, pyridines, quinolines, isoquinolines, anilines, aminocarboxylic acids, and the like.
[0044] The amines are preferably sulfonic acid group-containing alkylene oxide adduct amines. Since the sulfonic acid group-containing alkylene oxide adduct amines have an alkylene oxide added thereto, they are classified as polymer surfactants as described above, but can also be classified as amines, and are effective as levelers.
[0045] Specific examples of nitrogen-containing organic compounds other than the above-mentioned amines that are effective as levelers include toluidine dyes such as CI (Color Index) Basic Red 2 and Toluidine Blue, azo dyes such as CI Direct Yellow 1 and CI Basic Black 2, phenazine dyes such as 3-amino-6-dimethylamino-2-methylphenazine 1 hydrochloride, polyethyleneimine, a copolymer of diallylamine and allylguanidine methanesulfonate, EO and / or PO adducts of tetramethylethylenediamine, succinimide, imidazolines such as 2'-bis(2-imidazoline), imidazoles, benzimidazoles, indoles, pyridines such as 2-vinylpyridine, 4-acetylpyridine, 4-mercapto-2-carboxylpyridine, 2,2'-bipyridyl, and phenanthroline, quinolines, isoquinolines, and aniline. Examples of the dyes include 3,3',3"-nitrilo-3-propionic acid and diaminomethyleneaminoacetic acid. Among these, preferred are toluidine dyes such as CI Basic Red 2, azo dyes such as CI Direct Yellow 1, phenazine dyes such as 3-amino-6-dimethylamino-2-methylphenazine 1 hydrochloride, polyethyleneimine, a copolymer of diallylamine and allylguanidine methanesulfonate, EO and PO adducts of tetramethylethylenediamine, imidazolines such as 2'-bis(2-imidazoline), benzimidazoles, pyridines such as 2-vinylpyridine, 4-acetylpyridine, 2,2'-bipyridyl, and phenanthroline, quinolines, anilines, and aminocarboxylic acids such as aminomethyleneaminoacetic acid.
[0046] Examples of the pH buffering agent include monocarboxylic acids such as formic acid, acetic acid, and propionic acid, dicarboxylic acids such as boric acids, phosphoric acids, oxalic acid, and succinic acid, oxycarboxylic acids such as lactic acid, tartaric acid, citric acid, malic acid, and isocitric acid, and oxo acids such as boric acid, metaboric acid, and tetraboric acid.
[0047] The chelating agent may include, for example, oxycarboxylic acid, polycarboxylic acid, monocarboxylic acid, etc., some of which are the same as the examples of the electrolytes and acids as the pH buffering agents. Specifically, for example, gluconic acid, citric acid, glucoheptonic acid, gluconolactone, glucoheptolactone, formic acid, acetic acid, propionic acid, butyric acid, ascorbic acid, oxalic acid, malonic acid, succinic acid, glycolic acid, malic acid, tartaric acid, diglycolic acid, and salts thereof may be used. Further examples include ethylenediamine, ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), nitrilotriacetic acid (NTA), iminodiacetic acid (IDA), iminodipropionic acid (IDP), hydroxyethylethylenediaminetriacetic acid (HEDTA), triethylenetetraminehexaacetic acid (TTHA), ethylenedioxybis(ethylamine)-N,N,N',N'-tetraacetic acid, glycines, nitrilotrimethylphosphonic acid, 1-hydroxyethane-1,1-diphosphonic acid, and salts thereof.
[0048] The contents of the various additives in the electrolytic copper plating or copper alloy plating bath are not particularly limited, and may be appropriately adjusted so that the desired structure is formed from the plating bath.
[0049] The electrolytic copper plating or copper alloy plating bath can be prepared by appropriately mixing, for example, one or more copper ion supplying compounds, one or more soluble salts of metals that form alloys with copper, and various additives such as electrolytes, accelerators, polymeric surfactants, levelers, pH buffers, and chelating agents.
[0050] The copper plating layer or copper alloy plating layer constituting the structure of the present invention can be formed by performing an electroplating process on the electroplating copper or copper alloy plating bath, and the electroplating process has a significant feature. That is, after performing an electroplating process on an electroplating copper or copper alloy plating bath at a predetermined first cathode current density, the electroplating process is terminated by changing the second cathode current density lower than the first cathode current density to form a copper plating layer or copper alloy plating layer. By performing an electroplating process with a cathode current density at the end lower than the previous cathode current density in this way, it is possible to suppress the generation of Kirkendall voids at the bonding interface between the copper plating layer or copper alloy plating layer and, for example, a plating layer of a metal or metal alloy other than copper described later, which is caused by the difference in the diffusion speed of each metal.
[0051] The change from a predetermined first cathode current density to a second cathode current density lower than the first cathode current density is performed in the final stage of forming the copper plating layer or the copper alloy plating layer, which refers to the stage of forming the surface layer of the copper plating layer or the copper alloy plating layer.
[0052] In the structure of the present invention (I), the predetermined first cathode current density is the cathode current density in an electroplating process carried out at a single cathode current density until it is changed to the second cathode current density.
[0053] The electroplating process performed at a single cathode current density is an electroplating process performed with the cathode current density at the start set as the first cathode current density without changing the cathode current density at the start. That is, after the plating process is started at a predetermined first cathode current density, the cathode current density is lowered only at the final stage of forming the copper plating layer or copper alloy plating layer. This lowered cathode current density is the second cathode current density.
[0054] In the structure of the present invention (II), the predetermined first cathode current density is an average cathode current density in an electroplating process performed by combining a plurality of cathode current densities until the second cathode current density is changed.
[0055] The electroplating process performed with a combination of a plurality of cathode current densities is an electroplating process performed by changing the cathode current density at least once from the start to the final stage of forming a copper plating layer or a copper alloy plating layer.
[0056] That is, in the present invention (II), the cathode current density may be increased or decreased any number of times from the start to the final stage. Examples of electroplating processes using a combination of a plurality of cathode current densities include electroplating processes using a combination of a cathode current density that is increased in sequence from the start to the final stage, electroplating processes using a combination of a cathode current density that is decreased in sequence, electroplating processes including an increase and then a decrease in the cathode current density, and electroplating processes including an increase and then a decrease in the cathode current density. Among these electroplating processes using a combination of a plurality of cathode current densities, the electroplating processes using a combination of a cathode current density that is increased in sequence and the electroplating processes including an increase and then a decrease in the cathode current density are preferred because they have a significant effect of suppressing the generation of Kirkendall voids, particularly when electroplating is performed on an electrolytic copper plating or copper alloy plating bath at high speed plating.
[0057] Then, the average cathode current density from the start to the final stage is set as a predetermined first cathode current density, and the first cathode current density is lowered in the final stage. This lowered cathode current density is the second cathode current density.
[0058] The average cathode current density is calculated by the following formula (1). Average cathode current density = cathode current density n1 × (Plating time n1 / total plating time) +Cathode current density n2 × (Plating time n2 / total plating time)... +Cathode current density n-1 × (Plating time n-1 / total plating time) +Cathode current density n × (Plating timen / total plating time) (1) (wherein the plurality of cathode current densities is n cathode current densities, Cathode current density n1 is the first cathode current density, Cathode current density n2 is the second cathode current density, Cathode current density n-1 is the n-1th cathode current density, Cathode current density n is the nth cathode current density, Plating Time n1 is the cathode current density n1 The plating time was Plating Time n2 is the cathode current density n2 The plating time was... Plating Time n-1 is the cathode current density n-1 The plating time was Plating Time n is the cathode current density n (The plating time was
[0059] The predetermined first cathode current density is set to 5 A / dm from the viewpoint of productivity of the structure. 2 More than 7A / dm, preferably 2 That's all.
[0060] The second cathode current density is 1 A / dm 2 ~4A / dm 2 It is preferable to set the current to 1.5A / dm 2 ~3.0A / dm 2 It is more preferable that the second cathode current density is set to be less than the lower limit, the formation of the surface layer portion may be insufficient. If the second cathode current density is greater than the upper limit, the suppression of the generation of Kirkendall voids may be insufficient. There is no particular limitation on the difference between the set value of the first cathode current density and the set value of the second cathode current density, and the second cathode current density may be set to be lower than the first cathode current density.
[0061] Similarly to the first cathode current density, the second cathode current density may be a cathode current density in an electroplating process performed at a single cathode current density, or may be an average cathode current density in an electroplating process performed by combining a plurality of cathode current densities. The average cathode current density is calculated from the formula (1) in the same manner as the average cathode current density of the first cathode current density.
[0062] As described above, by changing the cathode current density to the second cathode current density lower than the first cathode current density, the surface layer of the copper plating layer or copper alloy plating layer is formed to a thickness of 0.05 μm to 15 μm, preferably 0.5 μm to 10 μm. If the thickness of the surface layer is less than the lower limit, the suppression of the generation of Kirkendall voids is insufficient. Conversely, if the thickness of the surface layer exceeds the upper limit, it is disadvantageous in terms of productivity of the structure.
[0063] There is no particular limitation on the thickness of the entire copper plating layer or copper alloy plating layer including the surface layer, but considering that the structure will be used as, for example, a protruding electrode, it is preferably about 15 μm to 250 μm.
[0064] When performing electroplating in the copper electroplating or copper alloy plating bath, various plating methods can be used, such as barrel plating, rack plating, high-speed continuous plating, rackless plating, cup plating, dip plating, etc. The temperature of the copper electroplating or copper alloy plating bath is not particularly limited, and is preferably, for example, 0°C or higher, and more preferably about 10°C to 50°C.
[0065] The structure of the present invention includes the copper plating layer or copper alloy plating layer, and preferably includes a plating layer of a metal or metal alloy other than copper adjacent to the copper plating layer or copper alloy plating layer. By including the plating layer of a metal or metal alloy other than copper, the structure of the present invention can be used in a wide range of applications, for example as a protruding electrode.
[0066] The metal other than copper is not particularly limited, and examples thereof include tin, silver, zinc, nickel, bismuth, cobalt, indium, antimony, gold, lead, etc. As described above, the metal other than copper may be selected from among metals that form alloys together with copper.
[0067] The plating layer of a metal or metal alloy other than copper is formed by electroplating in an electroplating bath of a metal or metal alloy other than copper so as to be adjacent to the copper plating layer or copper alloy plating layer.
[0068] The electroplating bath for the metal other than copper is preferably blended with, for example, one or more ion supply compounds of the metal, and the electroplating bath for the metal alloy other than copper is preferably blended with, for example, one or more ion supply compounds of the metal for each of the two or more metals constituting the alloy. The metal ion supply compound is not particularly limited as long as it is a soluble salt that basically generates metal ions in an aqueous solution.
[0069] As the soluble salts of each metal, for example, soluble salts of tin, soluble salts of silver, soluble salts of zinc, soluble salts of nickel, soluble salts of bismuth, soluble salts of cobalt, soluble salts of indium, soluble salts of antimony, soluble salts of gold, soluble salts of lead, etc., there may be mentioned those exemplified as the soluble salts that can be incorporated into the electric copper alloy plating bath.
[0070] The content of the metal ion supply compound in the electroplating bath for metals or metal alloys other than copper is not particularly limited, but is preferably about 1 g / L to 200 g / L, more preferably about 10 g / L to 150 g / L.
[0071] There are no particular limitations on the combination and ratio of various metal ion supply compounds, and the combination and ratio may be appropriately adjusted so that the structure of the present invention having a plating layer of a metal or metal alloy other than copper adjacent to a copper plating layer or copper alloy plating layer has the desired composition.
[0072] Among the plating layers of various metals or metal alloys other than copper, a tin plating layer or a tin alloy plating layer is preferred. A structure in which the tin plating layer or the tin alloy plating layer is provided adjacent to the copper plating layer or the copper alloy plating layer can be used, for example, as a protruding electrode with superior performance.
[0073] In addition to the ion supplying compounds of the various metals described above, various additives such as electrolytes, accelerators, polymeric surfactants, levelers, pH buffers, chelating agents, etc. may be blended into electroplating baths for metals or metal alloys other than copper. Examples of these various additives include those exemplified as the various additives that can be blended into the electrolytic copper or copper alloy plating baths described above.
[0074] The contents of the various additives in the electroplating bath for a metal or metal alloy other than copper are not particularly limited, and may be appropriately adjusted so that a plating layer of the desired metal or metal alloy other than copper is formed adjacent to the copper plating layer or copper alloy plating layer.
[0075] An electroplating bath for a metal or metal alloy other than copper can be prepared by appropriately blending, for example, one or more metal ion supplying compounds, such as various additives such as electrolytes, accelerators, polymeric surfactants, levelers, pH buffers, and chelating agents.
[0076] When electroplating in an electroplating bath of a metal or metal alloy other than copper, various plating methods similar to those used when electroplating in the electroplating bath of copper or copper alloy can be used. There are no particular limitations on the conditions for electroplating in an electroplating bath of a metal or metal alloy other than copper. For example, the cathode current density is 0.001 A / dm 2 ~100A / dm 2 About 0.01A / dm 2 ~40A / dm 2 The bath temperature is preferably about 0°C or higher, and more preferably about 10°C to 50°C.
[0077] Thus, when a plating layer of a metal or metal alloy other than copper is formed adjacent to the copper plating layer or copper alloy plating layer, the sum of the thickness of the copper plating layer or copper alloy plating layer and the thickness of the plating layer of the metal or metal alloy other than copper is preferably 20 μm or more, more preferably 30 μm or more. If the sum of the thicknesses is less than the lower limit, the bonding strength between the copper plating layer or copper alloy plating layer and the plating layer of the metal or metal alloy other than copper may be insufficient. The upper limit of the sum of the thicknesses is not particularly limited, but is preferably 500 μm or less, considering that the structure is used as a protruding electrode, for example.
[0078] There is no particular limitation on the thickness of the plating layer of a metal or metal alloy other than copper, but in consideration of the bonding reliability between the copper plating layer or copper alloy plating layer and the plating layer of a metal or metal alloy other than copper, it is preferable that the thickness be approximately 5 μm to 100 μm.
[0079] Furthermore, when a plating layer of a metal or metal alloy other than copper is not formed, the copper or copper alloy deposited by the electroplating process can be reflowed as necessary to produce the desired structure, and when a plating layer of a metal or metal alloy other than copper is formed, the metal or metal alloy other than copper deposited by the electroplating process can be reflowed as necessary to produce the desired structure.
[0080] The structure of the present invention is, for example, a protruding electrode, and can be formed on electronic components such as a glass substrate, a silicon substrate, a sapphire substrate, a wafer, a printed wiring board, a semiconductor integrated circuit, a resistor, a variable resistor, a capacitor, a filter, an inductor, a thermistor, a quartz oscillator, a switch, a lead wire, and a solar cell. EXAMPLES
[0081] Below, we will sequentially describe examples of structure α having a copper plating layer or copper alloy plating layer of the present invention, and evaluation test examples of Kirkendall void formation for structure β having a plating layer of a metal or metal alloy other than copper adjacent to the copper plating layer or copper alloy plating layer of structure α.
[0082] However, the present invention is not limited to the above-mentioned Examples and Test Examples, and it goes without saying that any modifications can be made within the scope of the technical concept of the present invention.
[0083] [Structure of the present invention (I)] First, an example according to the structure of the present invention (I) (an example in which the first cathode current density is a single cathode current density) and a comparative example are shown.
[0084] <<Example of structure α having copper plating layer or copper alloy plating layer>> Among the following Examples I-1 to I-9, Examples I-1 to I-8 are examples of structures α provided with a copper plating layer, and Example I-9 is an example of structure α provided with a copper-nickel alloy plating layer.
[0085] Comparative Examples I-1 and I-2 are examples of structure α having a copper plating layer, and Comparative Example I-3 is an example of structure α having a copper-nickel alloy plating layer. Comparative Examples I-1 and I-3 are blank examples in which the second cathode current density is not set, and Comparative Example I-2 is a blank example in which the thickness of the surface layer is less than 0.05 μm.
[0086] (1) Example I-1 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10A / dm 2 Plating time: about 550 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: about 180 seconds Thickness of the formed surface layer: 2μm
[0087] (2) Example I-2 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 5A / dm 2 Plating time: about 1100 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: about 180 seconds Thickness of the formed surface layer: 2μm
[0088] (3) Example I-3 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 15A / dm 2 Plating time: Approximately 370 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: about 180 seconds Thickness of the formed surface layer: 2μm
[0089] (4) Example I-4 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10A / dm 2 Plating time: about 550 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 2A / dm 2 Plating time: about 270 seconds Thickness of the formed surface layer: 2μm
[0090] (5) Example I-5 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10A / dm 2 Plating time: about 550 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: about 90 seconds Thickness of the formed surface layer: 1μm
[0091] (6) Example I-6 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10A / dm 2 Plating time: about 550 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: Approximately 450 seconds Thickness of the formed surface layer: 5μm
[0092] (7) Example I-7 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyoxyethylene alkyl ether (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10A / dm 2 Plating time: about 550 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: about 180 seconds Thickness of the formed surface layer: 2μm
[0093] (8) Example I-8 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyoxyethylene alkyl ether (average molecular weight 1000): 100 mg / L 2-Methylimidazole: 2 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10A / dm 2 Plating time: about 550 seconds Thickness of copper plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: about 180 seconds Thickness of the formed surface layer: 2μm
[0094] (9) Example I-9 An electric copper-nickel alloy plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 10g / L Nickel sulfate (Ni 2+ As: 50g / L Sulfuric acid (as free acid): 20g / L Hydrochloric acid (as chloride ion): 80 mg / L Boric acid (as a pH buffer): 20g / L EDTA (as a chelating agent): 120g / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 5A / dm 2 Plating time: Approximately 1180 seconds Thickness of copper-nickel alloy plating layer formed: 20μm (c) After changing the cathode current density 2nd cathode current density: 2A / dm 2 Plating time: Approximately 440 seconds Thickness of the formed surface layer: 3μm (D) Other pH: 4.0 (adjusted with NaOH)
[0095] (10) Comparative example I-1 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] Bath temperature: 30℃ Cathode current density (unchanged): 10A / dm 2 Plating time: Approximately 630 seconds Thickness of copper plating layer formed (total): 23μm
[0096] (11) Comparative example I-2 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 5A / dm 2 Plating time: Approximately 1200 seconds Thickness of copper plating layer formed: 22μm (c) After changing the cathode current density 2nd cathode current density: 3A / dm 2 Plating time: about 20 seconds The thickness of the surface layer formed: 0.03μm
[0097] (12) Comparative example I-3 An electric copper-nickel alloy plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 10g / L Nickel sulfate (Ni 2+ As: 50g / L Sulfuric acid (as free acid): 20g / L Hydrochloric acid (as chloride ion): 80 mg / L Boric acid (as a pH buffer): 20g / L EDTA (as a chelating agent): 120g / L [Plating conditions] Bath temperature: 30℃ Cathode current density (unchanged): 5A / dm 2 Plating time: about 1350 seconds Thickness of copper-nickel alloy plating layer formed (total): 23μm pH: 4.0 (adjusted with NaOH)
[0098] <Example of structure β having tin-silver alloy plating layer> Next, a tin-silver alloy plating layer was formed on the copper plating layer of the structure α of Examples I-1 to I-8 and Comparative Examples I-1 to I-2, and on the copper-nickel alloy plating layer of the structure α of Example I-9 and Comparative Example I-3, to manufacture the structure β. The composition of the electric tin-silver alloy plating bath and plating conditions are shown below. [composition] Stannous methanesulfonate (Sn 2+ As: 50g / L Silver methanesulfonate (Ag + As: 0.3g / L Methanesulfonic acid: 100g / L Catechol (as an antioxidant): 0.5g / L Bisphenol A polyethoxylate (EO 13 moles): 5g / L Sodium alkylnaphthalene sulfonate: 1g / L 5'5-Dithiobis(1-phenyl-1H-tetrazole) (as a complexing agent): 5g / L [Plating conditions] Bath temperature: 25℃ Cathode current density: 3A / dm 2 Plating time: Approximately 800 seconds The thickness of the formed tin-silver alloy plating layer: 20μm
[0099] <Example of evaluation test for Kirkendall void generation> The obtained structure β was reflowed and heat-treated at 150°C for 200 hours. Then, the cross section of the structure β was processed by ion milling, and the cross section of the Kirkendall voids was observed by a field emission scanning electron microscope (FE-SEM). The size and amount of the Kirkendall voids were confirmed from the observed field of view and evaluated based on the following evaluation criteria. The results are shown in Table 1. [Evaluation Criteria] ◎: No Kirkendall voids were observed. ◯: Less than five Kirkendall voids less than 1 μm in size were observed, and no Kirkendall voids greater than 1 μm in size were observed. △: 5 to less than 50 Kirkendall voids less than 1 μm in size were confirmed, and / or less than 5 Kirkendall voids 1 μm or more in size were confirmed. ×: 50 or more Kirkendall voids with a size of less than 1 μm were observed, or 5 or more Kirkendall voids with a size of 1 μm or more were observed. XX: 50 or more Kirkendall voids less than 1 μm in size were confirmed, and 5 or more Kirkendall voids 1 μm or more in size were confirmed.
[0100] Table 1 also shows the metal types in the plating bath and the plating conditions.
[0101] [Table 1]
[0102] From Table 1 above, the following can be seen.
[0103] In comparison with Comparative Example I-1, in which a copper plating layer was formed without changing the cathode current density as in the conventional method, it was confirmed that no Kirkendall voids were generated in the structure of Example I-1, in which the surface portion of the copper plating layer was formed at a second cathode current density lower than the first cathode current density, and thus a significant improvement was achieved.
[0104] Generally, when the cathode current density is increased in copper electroplating, the generation of Kirkendall voids tends to increase. However, even in Example I-3, in which the first cathode current density is set higher than in Examples I-1 and I-2, it is possible to manufacture a structure in which the generation of Kirkendall voids is suppressed by forming the surface portion of the copper plating layer at a second cathode current density lower than the first cathode current density.
[0105] Even when the surface layer of the copper plating layer formed at the second cathode current density lower than the first cathode current density is thin as in Example I-5, a certain effect of suppressing the generation of Kirkendall voids is observed. However, when the surface layer is too thin, such as less than 0.05 μm as in Comparative Example I-2, the generation of Kirkendall voids cannot be sufficiently suppressed.
[0106] Even if the composition of the copper electroplating bath is changed as in Example I-7, the generation of Kirkendall voids can be sufficiently suppressed. Also, even if an copper electroplating bath containing a leveler is used as in Example I-8, the generation of Kirkendall voids can be sufficiently suppressed.
[0107] In addition, compared to Comparative Example I-3 in which a copper alloy plating layer was formed without changing the cathode current density as in the conventional method, the structure of Example I-9 in which the surface portion of the copper alloy plating layer was formed at a second cathode current density lower than the first cathode current density was confirmed to have a sufficient improvement in terms of suppressing the generation of Kirkendall voids.
[0108] [Structure of the present invention (II)] Next, an example of the structure of the present invention (II) (an example in which the first cathode current density is an average cathode current density of a plurality of cathode current densities) and a comparative example will be shown.
[0109] <<Example of structure α having copper plating layer or copper alloy plating layer>> Among the following Examples II-1 to II-16, Examples II-1 to II-13 are examples of structure α having a copper plating layer, Examples II-14 and II-15 are examples of structure α having a copper-nickel alloy plating layer, and Example II-16 is an example of structure α having a copper-silver alloy plating layer.
[0110] Comparative Examples II-1 to II-2 are examples of the structure α having a copper plating layer, Comparative Example II-3 is an example of the structure α having a copper-nickel alloy plating layer, and Comparative Example II-4 is an example of the structure α having a copper-silver alloy plating layer. Comparative Examples II-1 to II-4 are blank examples in which the second cathode current density is not set.
[0111] (1) Example II-1 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →15.0A / dm 2 Change to the order (Average cathode current density: approx. 14.1A / dm 2 ) Plating time: 27.1 seconds and 357.7 seconds respectively (Total: 384.8 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0112] (2) Example II-2 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 5.0A / dm 2 →10.0A / dm 2 Change to the order (Average cathode current density: approx. 9.9A / dm 2 ) Plating time: 10.8 seconds and 536.6 seconds respectively (Total: 547.4 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0113] (3) Example II-3 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10.0A / dm 2 →20.0A / dm 2 Change to the order (Average cathode current density: approx. 19.0A / dm 2 ) Plating time: 27.1 seconds and 257.5 seconds respectively (Total: 284.6 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0114] (4) Example II-4 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10.0A / dm 2 →20.0A / dm 2 Change to the order (Average cathode current density: approx. 19.0A / dm 2 ) Plating time: 27.1 seconds and 257.5 seconds respectively (Total: 284.6 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 →2.0A / dm 2 Change to the order (Average cathode current density: approx. 2.6A / dm 2 ) Plating time: 180.7 seconds and 135.5 seconds respectively (Total: 316.2 seconds) Thickness of the formed surface layer: 3.0μm
[0115] (5) Example II-5 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →15.0A / dm 2 Change to the order (Average cathode current density: approx. 14.5A / dm 2 ) Plating time: 27.1 seconds and 719.1 seconds respectively (Total: 746.2 seconds) Thickness of copper plating layer formed: 40.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0116] (6) Example II-6 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →15.0A / dm 2 Change to the order (Average cathode current density: approx. 14.5A / dm 2 ) Plating time: 27.1 seconds and 719.1 seconds respectively (Total: 746.2 seconds) Thickness of copper plating layer formed: 40.0μm (c) After changing the cathode current density 2nd cathode current density: 1.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 1.0μm
[0117] (7) Example II-7 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →15.0A / dm 2 Change to the order (Average cathode current density: approx. 14.5A / dm 2 ) Plating time: 27.1 seconds and 719.1 seconds respectively (Total: 746.2 seconds) Thickness of copper plating layer formed: 40.0μm (c) After changing the cathode current density 2nd cathode current density: 0.5A / dm 2 Plating time: 542.0 seconds Thickness of the formed surface layer: 1.0μm
[0118] (8) Example II-8 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →10.0A / dm 2 →20.0A / dm 2 Change to the order (Average cathode current density: approx. 16.8A / dm 2 ) Plating time: 27.1 seconds, 54.2 seconds, and 241.2 seconds respectively (Total: 322.5 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0119] (9) Example II-9 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →5.0A / dm 2 →10.0A / dm 2 Change to the order (Average cathode current density: approx. 8.0A / dm 2 ) Plating time: 27.1 seconds, 222.2 seconds, and 425.5 seconds respectively (Total: 674.8 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 180.0 seconds Thickness of the formed surface layer: 2.0μm
[0120] (10) Example II-10 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →20.0A / dm 2 →10.0A / dm 2 Change to the order (Average cathode current density: approx. 10.1A / dm 2 ) Plating time: 27.1 seconds, 27.1 seconds, 482.4 seconds respectively (Total: 536.6 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0121] (11) Example II-11 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10.0A / dm 2 →20.0A / dm 2 →15.0A / dm 2 Change to the order (Average cathode current density: approx. 15.3A / dm 2 ) Plating time: 5.4 seconds, 27.1 seconds, and 321.6 seconds respectively (Total: 354.1 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0122] (12) Example II-12 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10.0A / dm 2 →5.0A / dm 2 →2.0A / dm 2 Change to the order (Average cathode current density: approx. 5.9A / dm 2 ) Plating time: 406.5 seconds, 108.4 seconds, 406.5 seconds respectively (Total: 921.4 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0123] (13) Example II-13 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 10.0A / dm 2 →2.0A / dm 2 →20.0A / dm 2 Change to the order (Average cathode current density: approx. 7.5A / dm 2 ) Plating time: 406.5 seconds, 271.0 seconds, and 40.7 seconds respectively (Total: 718.2 seconds) Thickness of copper plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0124] (14) Example II-14 An electric copper-nickel alloy plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ as): 2.5g / L Nickel sulfate (Ni 2+ As: 70g / L Sulfuric acid (as free acid): 20g / L Hydrochloric acid (as chloride ion): 80 mg / L Boric acid (as a pH buffer): 20g / L EDTA (as a chelating agent): 120g / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2A / dm 2 →10A / dm 2 Change to the order (Average cathode current density: approx. 9.6A / dm 2 ) Plating time: 27.1 seconds and 536.6 seconds respectively (Total: 563.7 seconds) Thickness of the copper-nickel alloy plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm (D) Other pH: 4.0 (adjusted with NaOH)
[0125] (15) Example II-15 An electric copper-nickel alloy plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ as): 2.5g / L Nickel sulfate (Ni 2+ As: 70g / L Sulfuric acid (as free acid): 20g / L Hydrochloric acid (as chloride ion): 80 mg / L Boric acid (as a pH buffer): 20g / L EDTA (as a chelating agent): 120g / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 1.0A / dm 2 →5.0A / dm 2 →8.0A / dm 2 Change to the order (Average cathode current density: approx. 7.0A / dm 2 ) Plating time: 54.2 seconds, 135.5 seconds, 586.0 seconds respectively (Total: 775.7 seconds) Thickness of the copper-nickel alloy plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 2.0A / dm 2 Plating time: 440.0 seconds Thickness of the formed surface layer: 3.0μm (D) Other pH: 4.0 (adjusted with NaOH)
[0126] (16) Example II-16 An electric copper-silver alloy plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ as): 50.0g / L Silver methanesulfonate (Ag + As: 0.013g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L DL-Methionine (as a chelating agent): 5g / L Polyethylene glycol (average molecular weight 1000): 1000 mg / L [Plating conditions] (A) Bath temperature: 30℃ (a) Before changing the cathode current density 1st cathode current density: 2.0A / dm 2 →10.0A / dm 2 Change to the order (Average cathode current density: approx. 9.6A / dm 2 ) Plating time: 27.1 seconds and 536.6 seconds respectively (Total: 563.7 seconds) Thickness of copper-silver alloy plating layer formed: 20.0μm (c) After changing the cathode current density 2nd cathode current density: 3.0A / dm 2 Plating time: 271.0 seconds Thickness of the formed surface layer: 3.0μm
[0127] (17) Comparative Example II-1 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] Bath temperature: 30℃ Cathode current density (unchanged): 15.0A / dm 2 Plating time: 361.3 seconds Thickness of copper plating layer formed (total): 20.0 μm
[0128] (18) Comparative Example II-2 An electrolytic copper plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 50g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L Disodium 3,3'-dithiobis(1-propanesulfonate): 10mg / L Polyethylene glycol (average molecular weight 1000): 100 mg / L [Plating conditions] Bath temperature: 30℃ Cathode current density (unchanged): 10.0A / dm 2 Plating time: 542.0 seconds Thickness of copper plating layer formed (total): 20.0 μm
[0129] (19) Comparative Example II-3 An electric copper-nickel alloy plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ As: 10g / L Nickel sulfate (Ni 2+ As: 50g / L Sulfuric acid (as free acid): 20g / L Hydrochloric acid (as chloride ion): 80 mg / L Boric acid (as a pH buffer): 20g / L EDTA (as a chelating agent): 120g / L [Plating conditions] Bath temperature: 30℃ Cathode current density (unchanged): 10.0A / dm 2 Plating time: approx. 542.0 seconds Thickness of copper-nickel alloy plating layer formed (total): 20.0μm pH: 4.0 (adjusted with NaOH)
[0130] (20) Comparative Example II-4 An electric copper-silver alloy plating bath was prepared according to the following composition. The plating conditions are also shown below. [composition] Copper sulfate pentahydrate (Cu 2+ as): 50.0g / L Silver methanesulfonate (Ag + As: 0.013g / L Sulfuric acid (as free acid): 100g / L Hydrochloric acid (as chloride ion): 50 mg / L DL-Methionine (as a chelating agent): 5g / L Polyethylene glycol (average molecular weight 1000): 1000 mg / L [Plating conditions] Bath temperature: 30℃ Cathode current density (unchanged): 10.0A / dm 2 Plating time: approx. 542.0 seconds Thickness of copper-silver alloy plating layer formed (total): 20.0μm
[0131] <Example of structure β having tin-silver alloy plating layer> Next, a tin-silver alloy plating layer was formed on the copper plating layer of the structure α of Examples II-1 to II-13 and Comparative Examples II-1 to II-2, the copper-nickel alloy plating layer of the structure α of Examples II-14 to II-15 and Comparative Example II-3, and the copper-silver alloy plating layer of the structure α of Example II-16 and Comparative Example II-4 to manufacture the structure β. The composition of the electric tin-silver alloy plating bath and plating conditions are shown below. [composition] Stannous methanesulfonate (Sn 2+ As: 50g / L Silver methanesulfonate (Ag + As: 0.3g / L Methanesulfonic acid: 100g / L Catechol (as an antioxidant): 0.5g / L Bisphenol A polyethoxylate (EO 13 moles): 5g / L Sodium alkylnaphthalene sulfonate: 1g / L 5'5-Dithiobis(1-phenyl-1H-tetrazole) (as a complexing agent): 5g / L [Plating conditions] Bath temperature: 25℃ Cathode current density: 3A / dm 2 Plating time: Approximately 800 seconds The thickness of the formed tin-silver alloy plating layer: 20μm
[0132] <Example of evaluation test for Kirkendall void generation> The obtained structure β was reflowed and heat-treated at 180°C for 300 hours. Then, the cross section of the structure β was processed by ion milling, and the cross section of the Kirkendall voids was observed by a field emission scanning electron microscope (FE-SEM). The size and amount of the Kirkendall voids were confirmed from the observed field of view and evaluated based on the following evaluation criteria. The results are shown in Table 2-D. [Evaluation Criteria] ◎: No Kirkendall voids were observed. ◯: Less than five Kirkendall voids less than 1 μm in size were observed, and no Kirkendall voids greater than 1 μm in size were observed. △: 5 to less than 50 Kirkendall voids less than 1 μm in size were confirmed, and / or less than 5 Kirkendall voids 1 μm or more in size were confirmed. ×: 50 or more Kirkendall voids with a size of less than 1 μm were observed, or 5 or more Kirkendall voids with a size of 1 μm or more were observed. XX: 50 or more Kirkendall voids less than 1 μm in size were confirmed, and 5 or more Kirkendall voids 1 μm or more in size were confirmed.
[0133] In addition, in Tables 2-A to 2-D, the metal types in the plating bath and the plating conditions are also shown.
[0134] [Table 2]
[0135] [Table 3]
[0136] [Table 4]
[0137] [Table 5]
[0138] The following can be seen from Tables 2-A to 2-D.
[0139] In comparison with Comparative Examples II-1 to II-2, in which a copper plating layer was formed without changing the cathode current density as in the conventional method, it was confirmed that the generation of Kirkendall voids was sufficiently suppressed in the structures of Examples II-1 to II-13, in which the surface portion of the copper plating layer was formed by setting the second cathode current density lower than the first cathode current density, which is the average cathode current density of multiple cathode current densities.
[0140] It can be seen that no Kirkendall voids are generated, and a significant improvement is achieved, not only when the first cathode current density is set to the average cathode current density of multiple cathode current densities that are increased along the way, as in Examples II-1 to II-3, but also when the second cathode current density is set to the average cathode current density of multiple cathode current densities, like the first cathode current density, as in Example II-4.
[0141] As in Example II-5, even when the first cathode current density was set to the average cathode current density of multiple cathode current densities increased along the way to form a thick copper plating layer, no Kirkendall voids were generated, and a significant improvement was observed.
[0142] As in Examples II-6 to II-7, when the first cathode current density is set to the average cathode current density of multiple cathode current densities increased along the way to form a thick copper plating layer, and the second cathode current density is reduced to form a thin surface layer, it can be seen that the generation of Kirkendall voids is sufficiently suppressed.
[0143] It can be seen that no Kirkendall voids are generated and a significant improvement is achieved even when the first cathode current density is the average cathode current density of multiple cathode current densities that are sequentially increased along the way, as in Examples II-8 to II-9, when it is the average cathode current density of multiple cathode current densities that are increased along the way and then decreased, as in Examples II-10 to II-11, when it is the average cathode current density of multiple cathode current densities that are sequentially decreased along the way, as in Example II-12, or when it is the average cathode current density of multiple cathode current densities that are decreased along the way and then increased, as in Example II-13.
[0144] In addition, compared with Comparative Example II-3 in which a copper-nickel alloy plating layer was formed without changing the cathode current density as in the conventional method, and Comparative Example II-4 in which a copper-silver alloy plating layer was formed, it was confirmed that the generation of Kirkendall voids was sufficiently suppressed in the structures of Examples II-14 to II-15 in which a surface portion of a copper-nickel alloy plating layer was formed by setting the second cathode current density lower than the first cathode current density, which is the average cathode current density of multiple cathode current densities, and in the structure of Example II-16 in which a surface portion of a copper-silver alloy plating layer was formed.
[0145] Furthermore, it can be seen that even when the first cathode current density is set to the average cathode current density of multiple cathode current densities which are sequentially increased along the way, as in Example II-15, the generation of Kirkendall voids is sufficiently suppressed.
[0146] In addition, in the structures of Examples II-1 to II-16, the generation of Kirkendall voids is sufficiently suppressed, even though the structures were subjected to heat treatment under harsher conditions of 180° C. and 300 hours. [Industrial Applicability]
[0147] The structure having the copper plating layer or copper alloy plating layer of the present invention can be formed, for example, as a protruding electrode on various electronic components, thereby imparting high reliability.
Claims
1. A copper plating layer or a copper alloy plating layer; A plating layer of a metal or metal alloy other than copper is provided adjacent to the copper plating layer or copper alloy plating layer. A structure comprising: the copper plating layer or copper alloy plating layer includes a surface layer portion having a thickness of 0.5 μm to 15 μm, and the plating layer of a metal or metal alloy other than copper is adjacent to the surface layer portion; The plating layer of a metal or metal alloy other than copper is a plating layer of tin or a tin-silver alloy (provided that neither tin nor silver forms an alloy with copper in the copper alloy plating layer); When the structure is heat-treated at 150° C. for 200 hours or at 180° C. for 300 hours, at the bonding interface between the surface layer and the plating layer of the metal or metal alloy other than copper, Kirkendall voids are not present or There are less than 5 Kirkendall voids less than 1 μm in size, and there are no Kirkendall voids greater than 1 μm in size. structure.
2. 2. The structure according to claim 1, wherein the sum of the thickness of the copper plating layer or copper alloy plating layer and the thickness of the plating layer of a metal or metal alloy other than copper is 20 μm to 500 μm.
3. The structure according to claim 1 or 2, which is a protruding electrode.
4. A copper plating layer or a copper alloy plating layer; A plating layer of a metal or metal alloy other than copper is provided adjacent to the copper plating layer or copper alloy plating layer. A method for manufacturing a structure comprising: a step of performing an electroplating process at a predetermined first cathode current density in an electrolytic copper plating or copper alloy plating bath, and then changing the current density to a second cathode current density lower than the first cathode current density and terminating the electroplating process, thereby forming the copper plating layer or copper alloy plating layer; Then, the plating layer is formed adjacent to the copper plating layer or the copper alloy plating layer by performing an electroplating process in an electroplating bath of a metal or a metal alloy other than copper, the first predetermined cathode current density being a cathode current density in an electroplating process performed at a single cathode current density until a change to the second cathode current density is made; The predetermined first cathode current density is 5 A / dm 2 Set it to above By changing to the second cathode current density, a surface portion of the copper plating layer or copper alloy plating layer is formed, and a plating layer of a metal or metal alloy other than copper is formed adjacent to the surface portion; The thickness of the surface layer is 0.5 μm to 15 μm, The plating layer of a metal or metal alloy other than copper is a plating layer of tin or a tin-silver alloy (provided that neither tin nor silver forms an alloy with copper in the copper alloy plating layer); When the structure was heat-treated at 150° C. for 200 hours, at the bonding interface between the surface layer and the plating layer of the metal or metal alloy other than copper, Kirkendall voids are not present or There are less than 5 Kirkendall voids less than 1 μm in size, and there are no Kirkendall voids greater than 1 μm in size. Manufacturing method.
5. A copper plating layer or a copper alloy plating layer; A plating layer of a metal or metal alloy other than copper is provided adjacent to the copper plating layer or copper alloy plating layer. A method for manufacturing a structure comprising: a step of performing an electroplating process at a predetermined first cathode current density in an electrolytic copper plating or copper alloy plating bath, and then changing the current density to a second cathode current density lower than the first cathode current density and terminating the electroplating process, thereby forming the copper plating layer or copper alloy plating layer; Then, the plating layer is formed adjacent to the copper plating layer or the copper alloy plating layer by performing an electroplating process in an electroplating bath of a metal or a metal alloy other than copper, The predetermined first cathode current density is an average cathode current density calculated by the following formula (1) in an electroplating process performed by combining a plurality of cathode current densities until the predetermined first cathode current density is changed to the second cathode current density, Average cathode current density = cathode current density n1 × (Plating time n1 / total plating time) +Cathode current density n2 × (Plating time n2 / total plating time)... +Cathode current density n-1 × (Plating time n-1 / total plating time) +Cathode current density n × (Plating time n / total plating time) (1) (wherein the plurality of cathode current densities is n cathode current densities, cathode current density n1 is the first cathode current density, cathode current density n2 is the second cathode current density, ... cathode current density n-1 is the n-1th cathode current density, cathode current density n is the n-th cathode current density, Plating Time n1 is the cathode current density n1 The plating time was Plating Time n2 is the cathode current density n2 The plating time was... Plating Time n-1 is the cathode current density n-1 The plating time was Plating Time n is the cathode current density n (The plating time was The predetermined first cathode current density is 5 A / dm 2 Set it to above By changing to the second cathode current density, a surface portion of the copper plating layer or copper alloy plating layer is formed, and a plating layer of a metal or metal alloy other than copper is formed adjacent to the surface portion; The thickness of the surface layer is 0.5 μm to 15 μm, The plating layer of a metal or metal alloy other than copper is a plating layer of tin or a tin-silver alloy (provided that neither tin nor silver forms an alloy with copper in the copper alloy plating layer); When the structure was heat-treated at 180° C. for 300 hours, at the bonding interface between the surface layer and the plating layer of the metal or metal alloy other than copper, Kirkendall voids are not present or There are less than 5 Kirkendall voids less than 1 μm in size, and there are no Kirkendall voids greater than 1 μm in size. Manufacturing method.
6. 6. The method according to claim 5, wherein the electroplating process using a combination of a plurality of cathode current densities is an electroplating process in which the cathode current densities are sequentially increased or the cathode current density is increased and then decreased from the start of the electroplating process to the final stage of forming the copper plating layer or copper alloy plating layer.
Citation Information
Patent Citations
Method for continuously casting metal
JP1982056140A
Solder and solder ball for electronic device connection, and electronic device using the same
JP2004154845A
Copper plating method
JP2008308749A
Copper pillar with improved completeness and manufacturing method thereof
JP2019143243A
Electrochemical deposition method, electrochemical deposition apparatus and microstructure
WO2006038335A1